Innovative cultural inclusiveness in medical treatments (learning from the past) - Said, Mohamed Mohamed Tolba; Sawicka, Barbara; Umachandran, Krishnan (Oficyna Wydawnicza Stowarzyszenia Menedżerów Jakości i, 2018)
Innovation addresses major barriers to progress by migratory research through collaborative, interdisciplinary developmental initiatives. Critical thinking along with hands on skills to create, design involves a process of problem solving followed by creative and systemic action. Innovation in Medical treatments is cross cultural symbolizes a remarkable commonality of purpose among the patients to expand the benefit for the common good of people and their health which encourages immediate use and function. These cherished customizations bring change through a new drug combination or new treatment concerned. The critical factor in promoting medical innovation should include the areas affecting the essentials of life, development and modernization demands in people, technology use to control, reduce reasonably sustain the cost of activities, promote entertainment and appreciations of grey-areas. Intermedical-disciplinary initiatives and interactive innovation will benefit economy, increases treatment reliability and facilitates life with better utilization of resources. Medical education should also inspire learning other medical treatments by providing opportunity to all share their learning which when applied will bring newer thoughts to practice.